2016
DOI: 10.1080/09537104.2016.1184748
|View full text |Cite
|
Sign up to set email alerts
|

Routine transfusion of platelet concentrates effectively reduces reoperation rate for bleeding and pericardial effusion after elective operations for ascending aortic aneurysm

Abstract: Patients with ascending aortic aneurysm undergoing complex surgical procedures are at increased risk of early postoperative excessive blood loss. The aim of this study was to analyze safety and efficacy of routine transfusions of platelet (PLT) concentrates in reduction of hemorrhagic postoperative complications. The study involved 396 consecutive patients (289 males and 107 females) with the mean age of 55.9 ± 13.6 years who underwent elective operations for aortic aneurysms. They were divided retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Although coagulation diagnostics and management have improved over the years, perioperative bleeding is still a significant problem in cardiac surgery [Ghavidel 2015;Colson 2016;Perek 2016]. Bleeding tendency is probably inevitable these days, as recommendations of the latest guidelines, for example, advise operating while patients are on aspirin, and the growing use of novel oral anticoagulants that do not demand regular screening obfuscates the issue [Windecker 2014;Heidbuchel 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Although coagulation diagnostics and management have improved over the years, perioperative bleeding is still a significant problem in cardiac surgery [Ghavidel 2015;Colson 2016;Perek 2016]. Bleeding tendency is probably inevitable these days, as recommendations of the latest guidelines, for example, advise operating while patients are on aspirin, and the growing use of novel oral anticoagulants that do not demand regular screening obfuscates the issue [Windecker 2014;Heidbuchel 2015].…”
Section: Introductionmentioning
confidence: 99%
“…The AABB suggests platelet transfusion for patients having CPB who exhibit perioperative bleeding with thrombocytopenia and/or with evidence of platelet dysfunction.” . Conversely, Perek et al showed that routine transfusion of platelets to patients undergoing elective operations for ascending aortic aneurysm decreased risk of re‐intervention due to bleeding …”
Section: Discussionmentioning
confidence: 99%
“…Hence, platelet function defect and thrombocytopenia are commonly treated with transfusions of platelet in patients undergoing CPB. 33 Recently reported study on 177 patients observed thrombocytopenia in 167(94.4%) patients from the baseline value. There was maximum drop in platelet count during 2nd and 3rd postoperative days.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 94%